2008
DOI: 10.1111/j.1440-0960.2008.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Filaggrin and the great epidermal barrier grief

Abstract: One of the principal functions of human skin is to form an effective mechanical barrier against the external environment. This involves the maturation and death of epidermal keratinocytes as well as the assembly of a complex network of differentially and spatially expressed proteins, glycoproteins and lipids into the keratinocyte cell membrane and surrounding extracellular space. In 2006, the key role of the granular cell layer protein filaggrin (filament-aggregating protein) in maintaining the skin barrier wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 42 publications
1
27
0
2
Order By: Relevance
“…Importantly, a reduced amount of filaggrin, which is associated with reduced levels of hygroscopic amino acids and altered barrier functions, underlies ichthyosis vulgaris (OMIM 146700) and is a major risk factor for atopic dermatitis (OMIM 603165), two very common skin diseases often associated with rhinitis and asthma. The known reasons for filaggrin decrease are profilaggrin-gene null mutations [11][12][13] and cytokine-induced down-regulation [14,15]. Defective PAD activities can also be suspected since in vitro deimination of filaggrin increases its proteolysis by calpain I and bleomycin-hydrolase, two proteases involved in its processing in the lower stratum corneum [16].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, a reduced amount of filaggrin, which is associated with reduced levels of hygroscopic amino acids and altered barrier functions, underlies ichthyosis vulgaris (OMIM 146700) and is a major risk factor for atopic dermatitis (OMIM 603165), two very common skin diseases often associated with rhinitis and asthma. The known reasons for filaggrin decrease are profilaggrin-gene null mutations [11][12][13] and cytokine-induced down-regulation [14,15]. Defective PAD activities can also be suspected since in vitro deimination of filaggrin increases its proteolysis by calpain I and bleomycin-hydrolase, two proteases involved in its processing in the lower stratum corneum [16].…”
Section: Introductionmentioning
confidence: 99%
“…Using a candidate gene approach, common mutations in filaggrin gene (FLG, 1q21) have been implicated in the causation of ichthyosis vulgaris7779. Filaggrin80 (filament aggregation protein) is a major epidermal protein involved in maintaining the skin barrier81 and previous studies had demonstrated that filaggrin was absent or reduced in the skin cells of individuals with ichthyosis vulgaris82.…”
Section: Successes and Clinical Implicationsmentioning
confidence: 99%
“…Its precursor is rich in histidine, highly phosphorylated polypeptide-profilaggrin, which is the main component of the granularity of keratohyalin granular layer of epidermis [4]. Filaggrin metabolism is associated with an acidic pH of the stratum corneum, which is the optimal environment for the enzyme synthesizing lipids, and also contributes to the so-called natural moisturizing factor (NMF).…”
Section: Introductionmentioning
confidence: 99%